Reflections on Deanship - John Farrar (Bond Law Review)
The purpose of this article is to reflect on the experience of being Dean of three Law Faculties, Associate Deanof two and Acting Vice-Chancellor of one university, to express some opinion as to the characteristics thatmake a ‘good’ dean, and to caution others against repeating my mistakes. In doing so, the first thing that I willsay is that each university has its own characteristics and that university governance has changed considerablyin the last 30–40 years.